Processing behavior and mechanical properties of autopolymerizing hypoallergenic denture base polymers. Issue 5 (3rd September 2014) - Schellenberg, Jürgen; Otto, Tobias; Schadewald, Anke
ABSTRACT Driven by the phenomenon of increasing irritations and allergic reactions of dental prosthesis carriers preferably due to residual methyl methacrylate monomer in conventional dental materials, autopolymerizing hypoallergenic denture base polymers were prepared as two‐component materials in the shape of paste/paste‐ or powder/liquid systems. The processing behavior of these materials was investigated regarding the processing and solidification times also in dependence on the polymerization catalyst concentration, whereas the whole processing and curing characteristics and the final polymer properties were evaluated by dynamic mechanical analysis in shear mode in the temperature range from −145°C to 200°C. The mechanical properties of the hypoallergenic denture base polymers were validated regarding stiffness (flexural modulus E') and fracture toughness (maximum factor of loading intensity <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ch5618f" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Kmax</alternatives>, total work of fracture <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ch56190" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Wf</alternatives>) and the effects of monomer composition, kind of resin powder, impact modification by the liquid component, and water immersion on these properties were investigated. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41378.